The population ecology of muscina stabulans (fallen) (Diptera : Muscidae), along an urban-rural gradient of Buenos Aires, Argentina - Patitucci, Luciano D. (2010)
Fil: Patitucci, Luciano D. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.